The Invisibilization and Denial of Work in Argentinian Garment Homework - Burchielli, Rosaria; Delaney, Annie (Relations industrielles / Industrial Relations, 2016)
Homeworkers are a globally significant part of the informal workforce, commonly regarded as invisible because their work is not recognized (Burchielli et al., 2008; Prugl, 1999). In this qualitative study, we examine homeworker invisibility in the case of Argentinian garment homework using the concepts of work invisibilization and work denial.The work invisibilization concept (Krinsky and Simonet, 2012), referring to devalorized work resulting from the neoliberal agenda, is used to understand recent global trends away from standard work arrangements/protections. Arising from the social relations of domination, invisibilized work is precarious, with irregular/ non-existent employment contracts and relationships. Invisibilization thus provides a valuable lens for analysing homework, which shares key characteristics with emerging forms of invisibilized employment. Homework however, has not transformed but has always been informal, characterized by inferior standards. To account for this, we articulate a concept of denial of work.Cohen's (2001) concept of denial describes broad dimensions, including different forms, strategies and levels of denial. Adapting these, we construct a framework to analyze the denial of Argentinian garment homework, enabling a detailed examination of the specific social actors and processes involved in casting homework as non-work.In considering the denial of homework in relation to invisibilization, we argue that these are related but distinct concepts. Used together, they help explain the low-power condition of two types of garment homeworkers in Argentina while also accounting for their differences: the mostly male, migrant workers employed in clandestine workshops (such as the Bolivians interviewed in our study), and the traditional, mostly female, Argentinian garment homeworkers.Our findings suggest that Bolivian immigrant homeworkers are partially visibilized due to NGO advocacy. However, as there are no improvements to their working conditions, they remained largely invisibilized through the effects of capitalism. By contrast, traditional women homeworkers have no representation and internalize their condition: their invisibilization is explained by the cumulative effects of capitalism and patriarchy.